Second trimester uterine rupture: lesson learned - Abdulwahab, Dalia F; Ismail, Hamizah; Nusee, Zalina; Raja Ismail, Raja Arif Shah; M, Azam; Awang, Mokhtar; I, Roziah; Abd Rahman, Azlina; MS, Azrul (2011)
ntroduction: Uterine rupture is a rare obstetrics catastrophic especially if it occurs during early pregnancy. We experienced three cases of ruptured uterus in the second trimester that first line doctors and obstetrician could learn lessons from.